2022
DOI: 10.1080/11263504.2022.2100498
|View full text |Cite
|
Sign up to set email alerts
|

Temporal beta diversity patterns reveal global change impacts in closed mountain grasslands

Abstract: Global changes are recognized as one of the main drivers of biodiversity changes over time, especially in mountain ecosystems. A key approach to detect and investigate the effect of climate and land use change on these ecosystems is represented by vegetation surveys. In this study, based on the resurvey of historical vegetation data, we assessed temporal beta-diversity patterns within and between subalpine and alpine vegetation types in the Dolomiti Bellunesi National Park. Resurvey was focussed on plots sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…As with richness changes, these studies reveal considerable local variation, with some communities showing limited compositional change and others showing major changes in species identities and relative abundances (e.g. [133][134][135]).…”
Section: (B) Temporal Turnover In Compositionmentioning
confidence: 94%
See 1 more Smart Citation
“…As with richness changes, these studies reveal considerable local variation, with some communities showing limited compositional change and others showing major changes in species identities and relative abundances (e.g. [133][134][135]).…”
Section: (B) Temporal Turnover In Compositionmentioning
confidence: 94%
“…Because local temporal trends are spatially heterogeneous (e.g. [133][134][135]) and influenced by a number of drivers [136], it is difficult to predict how local compositional change scales up. For example, a study of ground beetles in Germany found evidence that local scale change did not lead to regional scale compositional and functional change [137].…”
Section: (B) Temporal Turnover In Compositionmentioning
confidence: 99%